Cognitive phenotypes of sequential staging in amyotrophic lateral sclerosis. (April 2018) - Lulé, Dorothée; Böhm, Sarah; Müller, Hans-Peter; Aho-Özhan, Helena; Keller, Jürgen; Gorges, Martin; Loose, Markus; Weishaupt, Jochen H.; Uttner, Ingo; Pinkhardt, Elmar; Kassubek, Jan; Del Tredici, Kelly; et al.
Abstract: Sequential spread of TDP-43 load in the brain may be a pathological characteristic of amyotrophic lateral sclerosis (ALS). Diffusion tensor imaging (DTI) is a magnetic resonance imaging (MRI) based marker of this pathological feature. Cognitive deficits known to be present in a subset of ALS patients might act as an additional in vivo clinical marker of disease spread. N = 139 patients with ALS were tested with the Edinburgh Cognitive and Behavioural ALS screen (ECAS) in addition to DTI brain measures of pathological spread. Executive function, memory and disinhibited behaviour were selected for Cognitive-Staging criteria, as these cognitive functions are attributed to cerebral areas analogous to the pattern of MRI markers of TDP-43 pathology. ROC curve analyses were performed to define cut-off scores for cognitive stages 2 (executive function), stage 3 (disinhibited behaviour) and stage 4 (memory), and staging was performed according to the cognitive profile subsequently. Associations of Cognitive-Staging (stage 2–4) and MRI-Staging measures were determined. In total, 77 patients (55%) performed below ROC cut-off scores in either executive function or memory or both and/or were reported to have disinhibited behaviour which permitted Cognitive-Staging. The cognitive profile of patients with discrete MRI stages 2–4 correlated significantly with DTI parameters. For those patients with cognitive impairment, there was a high congruency between MRI and Cognitive-Staging with high specificity and sensitivity of executive functions for MRI stage 2, disinhibited behaviour for MRI stage 3 and moderate of memory for MRI stage 4. Cognitive impairment follows specific patterns in ALS and these patterns can be used for Cognitive-Staging with a high specificity compared to MRI-Staging. For the individual, cognitive screening is a fast and easy to apply measurement of cerebral function giving valuable information in a clinical context. Graphical abstract: